The Challenges of Training Policy in Project Environment: Case of Tunisia - Mohamed Ali Hedhili; Sami Boudabbous (Journal of Business and Management Review, 2021)
Since the 1980s, the project has become an essential management approach for contemporary companies that require profound organizational transformations, hence the need for more in-depth studies on human resources development in this new environment. The present work aimed to recognize the different challenges of the training policy in the project environment. To this end, we conducted 31 semi-structured interviews with Tunisian project managers. The results showed that the training policy is a conducive context for skills development in the project environment. Project-based organizations are called upon to promote their employees’ skills through training programs encompassing mainly two kinds of skills: interpersonal and technical. The results also revealed that the temporary and unstable nature of the projects leaves little room for training due to time pressure, lack of budget, and work overload.